Try let $v=x+y$ , $w=x-y$ ,

Then $\dfrac{\partial u}{\partial x}=\dfrac{\partial u}{\partial w}\dfrac{\partial w}{\partial x}=\dfrac{\partial u}{\partial w}$

$\dfrac{\partial u}{\partial y}=\dfrac{\partial u}{\partial w}\dfrac{\partial w}{\partial y}=-\dfrac{\partial u}{\partial w}$

$\dfrac{\partial^2u}{\partial y^2}=\dfrac{\partial}{\partial y}\left(-\dfrac{\partial u}{\partial w}\right)=-\dfrac{\partial}{\partial v}\left(\dfrac{\partial u}{\partial w}\right)\dfrac{\partial v}{\partial y}=-\dfrac{\partial^2u}{\partial vw}$

$\therefore-\dfrac{\partial^2u}{\partial vw}=\dfrac{\partial u}{\partial w}$

Let $z=\dfrac{\partial u}{\partial w}$ ,

Then $\dfrac{\partial z}{\partial v}=\dfrac{\partial^2u}{\partial vw}$

$\therefore-\dfrac{\partial z}{\partial v}=z$



$\ln z=-v+c_1(w)$


$\dfrac{\partial u}{\partial w}=c_2(w)e^{-v}$

$u=\int c_2(w)e^{-v}~dw$



I did it correctly in Finding an analytical solution to the wave equation using method of characteristics , and did it not known whether correct or not in Solving $yu_{xx}+(x+y)u_{xy}+xu_{yy}=0$ , but why in here is wrong?

  • 8
    $\begingroup$ The second line is wrong. The multivariate chain rule is more complicated than this. $\endgroup$ – Qiaochu Yuan Jul 8 '12 at 23:12
  • $\begingroup$ so how is correctly transform $\dfrac{\partial u}{\partial x}=\dfrac{\partial^2u}{\partial y^2}$ to a 2nd order PDE by letting $v=x+y$ , $w=x-y$ ? $\endgroup$ – doraemonpaul Jul 9 '12 at 1:17

Fleshing out @QiaochuYuan's comment a little: $$\begin{eqnarray*} \frac{\partial}{\partial x} &=& \frac{\partial v}{\partial x} \frac{\partial}{\partial v} + \frac{\partial w}{\partial x} \frac{\partial}{\partial w} \\ &=& \frac{\partial}{\partial v} + \frac{\partial}{\partial w} \\ \frac{\partial}{\partial y} &=& \frac{\partial v}{\partial y} \frac{\partial}{\partial v} + \frac{\partial w}{\partial y} \frac{\partial}{\partial w} \\ &=& \frac{\partial}{\partial v} - \frac{\partial}{\partial w}. \\ \end{eqnarray*}$$ The reason this is a nice change of variables for the wave equation is because $$\frac{\partial^2}{\partial x^2} - \frac{\partial^2}{\partial y^2} = 4 \frac{\partial}{\partial v} \frac{\partial}{\partial w}.$$ No such nice thing happens with the heat equation.

Addendum: Note that $$\begin{eqnarray*} \frac{\partial^2}{\partial x^2} &=& \left(\frac{\partial}{\partial v} + \frac{\partial}{\partial w}\right)^2 \\ &=& \frac{\partial^2}{\partial v^2} + 2 \frac{\partial}{\partial v} \frac{\partial}{\partial w} + \frac{\partial^2}{\partial w^2} \\ \frac{\partial^2}{\partial y^2} &=& \left(\frac{\partial}{\partial v} - \frac{\partial}{\partial w}\right)^2 \\ &=& \frac{\partial^2}{\partial v^2} - 2 \frac{\partial}{\partial v} \frac{\partial}{\partial w} + \frac{\partial^2}{\partial w^2}. \\ \end{eqnarray*}$$ The transformed equation is  $$\left(\frac{\partial}{\partial v} + \frac{\partial}{\partial w}\right)u(v,w) = \left(\frac{\partial^2}{\partial v^2}     - 2 \frac{\partial}{\partial v} \frac{\partial}{\partial w}     + \frac{\partial^2}{\partial w^2}\right) u(v,w).$$ There are no nice cancelations. This transformation just makes the PDE harder to solve.

  • $\begingroup$ Your answer does not complete. How about $\dfrac{\partial^2u}{\partial x^2}$ and $\dfrac{\partial^2u}{\partial y^2}$ ? $\endgroup$ – doraemonpaul Jul 9 '12 at 1:20
  • $\begingroup$ @doraemonpaul: Added. $\endgroup$ – user26872 Jul 9 '12 at 1:26
  • $\begingroup$ How about $\dfrac{\partial^2u}{\partial xy}$ ? $\endgroup$ – doraemonpaul Jul 9 '12 at 1:37
  • $\begingroup$ @doraemonpaul: What is $(a+b)(a-b)$? $\endgroup$ – user26872 Jul 9 '12 at 1:41
  • $\begingroup$ $a^2-b^2$ . Do you mean $\dfrac{\partial^2u}{\partial xy}=\dfrac{\partial^2u}{\partial v^2}-\dfrac{\partial^2u}{\partial w^2}$ ? I don't understand why the partial derivative can first remove their dependent variable and then multiplicate each other? $\endgroup$ – doraemonpaul Jul 9 '12 at 2:16

This equation is a heat equation. Usually we use the methods of seperation of variables or Fourier transforms.

Seperation of variables: Let $$ u=X(x)*Y(y),$$ then we get $$X'(x)Y(y)=X(x)Y''(y).$$ That is to say, $$X'/X=Y''/Y$$ Notice that the left side of the equation above is a function of $x$, while the right side the function of $y$. So if the left side equals the right side, then both of them must be constant. Thus $$X'/X=c,Y''/Y=c,$$ these are ODEs which are easy to solve.

Fourier Transform: Notice that we use Fourier Transform with respect of $y.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.